Use of geographic information systems in iron and steel industry - Karaş, İsmail Rakıp; Demir, Sait (SILA SCIENCE, 2012)
Geographic Information Systems are information systems in which spatial data and non-spatial data are managed together. These data related to areas of factoring and production are allowed to be stored, processed, examined and analyzed together with the help of Geographic Information Systems, in contradistinction to other information systems. In our day, the use of Geographic Information Systems is becoming widespread in industrial foundations spread over large areas as a result of the fact that it contains extensive spatial data. Administrations such as inter-facility planning, synchronization of work groups, determining the most suitable areas through the use of environmental and spatial analyses based on location, optimization of production and transportation are some examples of this sort of usage. This paper is going to focus on the usability of Geographic Information Systems in iron-steel industry and bring forward proposals about Geographic Information Systems applications that can be implemented in an iron-steel plant. Advantages that will be gained through the use of Geographic Information Systems, time, cost and performance are going to be examined.
Keywords: Geographic information systems; Information systems; Iron-steel industry; Spatial analyses; Network analyses; Environmental analyses